Relacja między efektywnością a elastycznością organizacji - Osbert-Pociecha, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This article is an attempt to describe the linkages between efficiency and flexibility. Some theories of organization argue that efficiency requires a bureaucratic form of organization. There is no doubt that bureaucracy impedes flexibility so in the face of this contradiction it is necessary to find a special balance between efficiency and flexibility. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 337-349